The Reject : Community, Politics, and Religion after the Subject. - Goh, Irving (Commonalities Ser., 2014)
This book proposes the reject as the figure of thought for our contemporaneous times. It shows how the reject can open us to radical forms of relations, democratic horizons, and ""post-secular"" and ""posthuman"" futures not only beyond anthropocentric limits, but also in ways by which others and their differences are affirmed respectfully.